2021
DOI: 10.7575/aiac.alls.v.12n.3.p.73
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Writing on Google Docs: Taiwanese Students’ Participation, Behaviors, and Writing Trajectories with Real-work Online Tasks

Abstract: In the past two decades, the growing rage of computer mediated environments (CMC) affords new literacies and new opportunities for language learners to experience, construct, communicate, and access knowledge (Ware, Kern & Warschauer, 2016). Also, it suggests that writing in multimodal in the digital ear contributes to its production and interpretation (Canagarajah, 2013) and can be particularly beneficial for L2 learners’ writing practices (Elola & Oskoz, 2010) such as writing quality (Stroch, 2005), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This in-depth attention highlights the revolutionary potential of Web 2.0 technologies in enhancing students' writing skills. The frequency of these results demonstrates the significant contributions that digital platforms have made in facilitating writing practice (Liu et al, 2022;Sahla and Altalhab, 2022;Yousefifard and Fathi, 2021;Jong and Tan, 2021;Alghammas, 2020;Barrot, 2021), collaboration (Alghammas, 2020;Hsu, 2019;Yeh, 2021;Hafour and Al-Rashidy, 2020), and feedback systems (Hafour and Al-Rashidy, 2020;Alharbi, 2020;Sundrarajun, 2020;Ebadi, 2021;Sahla and Altalhab, 2022;Liu et al, 2022;Yousefifard and Fathi, 2021). Eleven investigations also showed a significant increase in participants' enthusiasm and motivation (Seifert and Har-Paz, 2020;Ballıdağ and Dikilitaş, 2021;Najjemba and Cronjé, 2020;Kung, 2018).…”
Section: Results Of the Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…This in-depth attention highlights the revolutionary potential of Web 2.0 technologies in enhancing students' writing skills. The frequency of these results demonstrates the significant contributions that digital platforms have made in facilitating writing practice (Liu et al, 2022;Sahla and Altalhab, 2022;Yousefifard and Fathi, 2021;Jong and Tan, 2021;Alghammas, 2020;Barrot, 2021), collaboration (Alghammas, 2020;Hsu, 2019;Yeh, 2021;Hafour and Al-Rashidy, 2020), and feedback systems (Hafour and Al-Rashidy, 2020;Alharbi, 2020;Sundrarajun, 2020;Ebadi, 2021;Sahla and Altalhab, 2022;Liu et al, 2022;Yousefifard and Fathi, 2021). Eleven investigations also showed a significant increase in participants' enthusiasm and motivation (Seifert and Har-Paz, 2020;Ballıdağ and Dikilitaş, 2021;Najjemba and Cronjé, 2020;Kung, 2018).…”
Section: Results Of the Studiesmentioning
confidence: 91%
“…The research also used Google Docs employed in nine investigations. The success of this application may be linked to its ability to edit collaborative documents, which makes it suitable for group projects and collaborative writing; both of these applications are essential for language acquisition (Chiablaem, 2021;Yeh, 2021;Hafour and Al-Rashidy, 2020;Ebadi, 2021;Alharbi, 2020). Finally, six studies used blogs as Web 2.0 tools.…”
Section: Web 20 Tools That Have Been Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a brief overview of the research results is needed to lay out how DMC has facilitated the learning process and what challenges emerged. In the studies, DMC was implemented to leverage students' English language skills, such as improving writing proficiency (e.g., Yeh, 2021;Balaman, 2018;Xu, 2021), oral presentation skills (e.g., Seau, Azamn, & Noor, 2018;Lee, 2019), and communicative competence (e.g., Greenblatt & Donald, 2022). Through DMC, the students also practiced their digital literacy skills by employing various multimodal resources (e.g., Jiang, 2022), which expanded their multiliteracies practice (e.g., Hung, 2019;Lo, Lee, & Tien, 2020;Yeh, 2018;Yeh, Heng, & Tseng, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Through the mixing and transmediating of the available semiotic resources, students expand their meaning-making by continuously reflecting on their design process. Moreover, research on DMC have indicated the benefits it brings to the language learning such as writing skill development and genre awareness (Yeh, et. al., 2021;Balaman, 2018;Yiqin, 2022), improved learning engagement and investment (Jiang, 2020;Smith, 2021), development of digital literacy skills (Yeh, 2018;Jiang, 2020), and practice on authorship (Hafner, 2015) and digital empathy (Chen, 2018;Christopher, 2021).…”
Section: Introductionmentioning
confidence: 99%